Cast away poems for our time - Nye, Naomi Shihab 1952- (Greenwillow Books, an imprint of HarperCollins Publishers, 2020)
"Poet Naomi Shihab Nye shines a spotlight on the things we cast away, from plastic water bottles to refugees"--
Includes index
Keywords: Recycling; Englisch; Kinderlyrik; Flüchtling; Umweltschutz; Jugendlyrik; Abfall; USA; Children's poetry, American; Children / Conduct of life / Juvenile poetry; Social action / Juvenile poetry; Environmental protection / Juvenile poetry; Refuse and refuse disposal / Poetry; Recycling (Waste) / Poetry; Refugees / Poetry; Ethics / Poetry; American poetry; JUVENILE NONFICTION / Poetry / General; JUVENILE NONFICTION / Science & Nature / Environmental Conservation & Protection; JUVENILE NONFICTION / Social Topics / Emigration & Immigration; Social action; Environmental protection; Children / Conduct of life; Children's poetry; NONFICTION / Poetry / General / JNF042000; Poetry; Juvenile works; Anthologie; Kinderbuch; Jugendbuch